Carbon Monoxide Poisoning: Saving Lives, Advancing Treatment - Baroness,Finlay of Llandaff I; Myers,I; Dickinson,R; Bennetto,L; Clarke,S; Eilersten-Feeney,K; Griffiths,L; Harrison,P; Humber,A; Jackson,G; Lewis,T; Mayho,B; et al. (All Party Parliamentary Group on Carbon Monoxide, 2017)
Carbon monoxide (CO) poisoning is a serious public health issue. In England and Wales alone, every year some 4,000 attendances to emergency departments (EDs) are the result of accidental CO poisoning. Statistics show that CO kills more than 30 people a year and leads to around 200 hospital admissions, but these figures are likely to be a gross underestimate. Consequently, treating accidental CO poisoning may actually be costing much more than the estimated £178 million per annum.Healthcare professionals have a vital role to play in preventing, diagnosing and treating patients exposed to CO. However, these professionals face a number of barriers to action: gaps in knowledge, limited awareness, and a lack of co-ordination within and between the healthcare sectors. These barriers need to be removed if we are to reduce significantly the number of accidental deaths and unnecessary injuries caused by CO poisoning, and to improve patient management and recovery.This report has been prepared by members of COMed, the healthcare professionals’ sub-group of the APPCOG Stakeholder Forum. It presents a number of hard-hitting essays that review current knowledge and practice on the diagnosis and management of CO poisoning in the healthcare system. It identifies gaps in knowledge and practice, and makes recommendations to close those gaps so that diagnosis, patient management and recovery can be improved.The findings presented in this report led members of the sub-group to conclude that:A lack of awareness amongst healthcare professionals of CO poisoning as a cause of illness is very likely to be impacting adversely on public health outcomes. Much remains to be discovered and explained about the link between low level chronic CO exposure and long-term effects on an individual’s health - for example, its impact on diseases of the cardiovascular and neurological system and whether CO is a casual factor of disease or involved in disease processes not previously